Detection and electrocatalytic mechanism of zearalenone using nanohybrid sensor based on copper-based metal-organic framework/magnetic Fe3O4-graphene oxide modified electrode. (15th February 2022) - Zeng, Yifang; Camarada, María Belén; Lu, Xinyu; Tang, Kaijie; Li, Weiqiang; Qiu, Daoyang; Wen, Yangping; Wu, Guoping; Luo, Qiushui; Bai, Ling
Highlights: Cu-based MOF was synthesized by Cu (II) ions and H3 BTC ligand. Nanohybrid sensor based on Cu-based MOF/Fe3 O4 -GO modified electrode was fabricated. The nanohybrid sensor was used to detect ZEA in spiked sample sensitively. The electrocatalytic mechanism of ZEA was proposed by DFT. Abstract: A novel and simple strategy was proposed for the determination of ZEA in breakfast cereal, maize powder and rice flour using an electrochemical nanohybrid sensor based on copper-based metal-organic framework (Cu-MOF)/magnetic Fe3 O4 -graphene oxide (Fe3 O4 -GO) modified electrode fabricated by the layer-by-layer assembled technique. The synthesized Cu-MOF with high porosity favorably improved the effective surface area and the analytical performance of nanohybrid sensing electrode. The crafted sensor has large surface area, high electron transfer, and satisfactory efficiency. ZEA was electrochemically detected in a wide linear range from 159.2 to 2865.2 ng mL −1 with LOD of 23.14 ng mL −1 under the optimal conditions. Moreover, the electrocatalytic mechanism of ZEA oxidation was proposed by density functional theory (DFT). A favorable energetic interaction was presented when Cu-MOF adsorbed on Fe3 O4 -GO, and a small new band appeared on the Fermi level energy ( Ef ) that facilitated the electron transfer between bands.